1996
DOI: 10.1093/nar/24.6.1059
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of tRNA (uracil-5-)-methyltransferase with NO2Ura-tRNA

Abstract: tRNA in which uracil is completely replaced by 5-nitro-uracil was prepared by substituting 5-nitro-UTP for UTP in an in vitro transcription reaction. The rationale was that the 5-nitro substituent activates the 6-carbon of the Ura heterocycle towards nucleophiles, and hence could provide mechanism-based inhibitors of enzymes which utilize this feature in their catalytic mechanism. When assayed shortly after mixing, the tRNA analog, NO2Ura-tRNA, is a potent competitive inhibitor of tRNA-Ura methyl transferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, this enzyme catalyzes in vitro methyl transfer to part of 16S rRNA (24). In the reaction, TrmA forms a covalent bond complex with substrate RNA (25,26), and methyl transfer takes place by a single displacement mechanism (27).…”
mentioning
confidence: 99%
“…Therefore, this enzyme catalyzes in vitro methyl transfer to part of 16S rRNA (24). In the reaction, TrmA forms a covalent bond complex with substrate RNA (25,26), and methyl transfer takes place by a single displacement mechanism (27).…”
mentioning
confidence: 99%
“…Furthermore, Ψ is a highly conserved modification at other sites in tRNA and in multiple RNA species. Substitution of 5-nitrouridine in tRNA was shown to trap tRNA-Ura methyl transferase (RUMT; [ 76 ]) by the formation of a reversible covalent complex in which Cys324 of RUMT forms a Michael adduct with NO 2 Ura54 in tRNA [ 77 ]. The role of TRMT2A, the mammalian tRNA methyltransferase 2 homolog A protein, for mammalian cell function remains unclear; however, a recent study demonstrated that TRMT2A-deficient cells displayed increased growth consistent with a role for TRMT2A in cell cycle regulation [ 78 ].…”
Section: Inhibition Of Rna Modification Enzymes and Rna-mediated Ementioning
confidence: 99%